Recent-onset dilated cardiomyopathy associated with Borrelia burgdorferi infection - Kuchynka, Petr; Palecek, Tomas; Havranek, Stepan; Vitkova, Ivana; Nemecek, Eduard; Trckova, Radka; Berenová, Dagmar; Krsek, Daniel; Podzimkova, Jana; Fikrle, Michal; Danek, Barbara Anna; Linhart, Ales (Herz, 2015)
BACKGROUND: Several recent small studies have suggested a causal link between Lyme disease and dilated cardiomyopathy (DCM) by demonstrating the presence of the Borrelia burgdorferi (Bb) genome in the myocardium of patients with recent-onset DCM. The aim of this study was to further investigate the effect of targeted antibiotic treatment of Bb-related recent-onset DCM in a larger cohort of patients. PATIENTS AND METHODS: We performed endomyocardial biopsy (EMB) in 110 individuals (53 ± 11 years, 34 women) with recent-onset unexplained DCM, and detected the Bb genome in 22 (20 %) subjects. Bb-positive patients were subsequently treated with intravenous ceftriaxone for 21 days in addition to conventional heart failure medication. RESULTS: At the 1-year follow-up, a significant improvement in left ventricular (LV) ejection fraction (26 ± 6 vs. 44 ± 12 %; p < 0.01) and a decrease in LV end-diastolic (69 ± 7 vs. 63 ± 11 mm; p < 0.01) and end-systolic (61 ± 9 vs. 52 ± 4 mm; p < 0.01) diameters were documented. Moreover, a significant improvement in heart failure symptoms (NYHA class 3.4 ± 0.6 vs. 1.5 ± 0.7; p < 0.01) was also observed. CONCLUSION: Targeted antibiotic treatment of Bb-related recent-onset DCM in addition to conventional heart failure therapy is associated with favorable cardiac remodeling and improvement of heart failure symptoms.
Keywords: Lyme disease; Anti-Bacterial Agents; Ceftriaxone; bakteriální endokarditida; výsledek terapie; Endomyocardial biopsy; Drug Therapy, Combination; Middle Aged; mužské pohlaví; Dilated cardiomyopathy; lymeská nemoc; Borrelia burgdorferi; Endocarditis, Bacterial; kombinovaná farmakoterapie; ženské pohlaví; Injections, Intravenous; Humans; Cardiomyopathy, Dilated; kardiotonika; dilatační kardiomyopatie; Cardiotonic Agents; antibakteriální látky; lidé středního věku; ceftriaxon; Lyme Disease; Antibiotics; injekce intravenózní; Female; Treatment Outcome; lidé; Male